2022
DOI: 10.3390/ph15030272
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Outcomes of Isatin and Its Derivatives against Multiple Diseases: Recent Developments in Drug Discovery

Abstract: Isatin (1H indole 2, 3-dione) is a heterocyclic, endogenous lead molecule recognized in humans and different plants. The isatin nucleus and its derivatives are owed the attention of researchers due to their diverse pharmacological activities such as anticancer, anti-TB, antifungal, antimicrobial, antioxidant, anti-inflammatory, anticonvulsant, anti-HIV, and so on. Many research chemists take advantage of the gentle structure of isatins, such as NH at position 1 and carbonyl functions at positions 2 and 3, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 94 publications
(97 reference statements)
1
24
0
Order By: Relevance
“…[17][18][19][20][21][22] In recent decades, the isatin (2,3-dioxindole) (I) molecule has attracted the concern of scientists for its potent biological and therapeutic applications. [23][24][25] Also, isatin derivatives have numerous distinct biological activities. Ethyl 4-chlorobenzoyl hydrazono-2-oxoindolin-1-yl acetate II is biologically active as a powerful in vitro inhibitor for an a-amylase enzyme (antidiabetic agent).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22] In recent decades, the isatin (2,3-dioxindole) (I) molecule has attracted the concern of scientists for its potent biological and therapeutic applications. [23][24][25] Also, isatin derivatives have numerous distinct biological activities. Ethyl 4-chlorobenzoyl hydrazono-2-oxoindolin-1-yl acetate II is biologically active as a powerful in vitro inhibitor for an a-amylase enzyme (antidiabetic agent).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, isatin (1H-Indole-2,3-dione) contains two reactive functional groups, including the amide and the ketone. It has been found that isatin itself does not exhibit any biological activity, but the derivatives containing this ring exhibit many interesting biological activities [7]. Many such compounds have been used as drugs in the treatment of human diseases, such indirubin, methisazone, NSC73306, semaxanib [8], sunitinib [9], and toceranib [10] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The isatin motif has surfaced as a privileged scaffold with numerous and significant pharmacological actions [ 13 ], such as antimicrobial [ 14 ], antiviral [ 15 ], and anticancer [ 16 ] effects. Noteworthy, isatin moiety has been included in some clinically approved medications such as Nintedanib and Sunitinib ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%